Edukasi Akad-Akad Keuangan Syariah Pada UMKM - Yuliyanti, Yuliyanti; Rahmawati, Iroh (Penerbit Widina, Widina Media Utama, 2025)
Micro, Small, and Medium Enterprises (UMKM) play a crucial role in Indonesia's economy. Many UMKM entrepreneurs face challenges in accessing financing that aligns with Islamic principles, primarily due to a lack of understanding of Islamic financial contracts. This community service activity aimed to improve the understanding of UMKM entrepreneurs regarding Islamic contracts such as murabahah, mudharabah, musyarakah, and ijarah, as well as provide information on how to access fairer and more transparent Islamic financing.This community service activity was held on Thursday, April 17, 2025, at the Mushola Lingkungan Kantin Royal, Serang, with 20 participants from the Dimsum Teh Ifat UMKM. The methods used included interactive training, discussions, and simulations. Pre-tests and post-tests were conducted to measure the improvement in participants' understanding. The pre-test results showed that only 40% of participants had a good understanding of Islamic contracts, whereas the post-test results indicated a significant improvement, with 85% of participants demonstrating better comprehension. The results of the activity showed a significant increase in participants' understanding of Islamic finance. Many participants expressed interest in accessing Islamic financing from Islamic cooperatives (BMT). The formation of a small UMKM Syariah community for further discussions indicated that the activity was well-received by the community. This initiative successfully improved financial literacy regarding Islamic finance among UMKM entrepreneurs and opened access to fairer financing in line with Islamic principles.ABSTRAKUsaha Mikro, Kecil, dan Menengah (UMKM) memiliki peran penting dalam perekonomian Indonesia. Banyak pelaku UMKM yang mengalami kesulitan dalam mengakses pembiayaan yang sesuai dengan prinsip syariah, terutama karena rendahnya pemahaman tentang akad-akad keuangan syariah. Kegiatan pengabdian ini bertujuan untuk meningkatkan pemahaman pelaku UMKM mengenai akad-akad syariah seperti murabahah, mudharabah, musyarakah, dan ijarah, serta memberikan informasi mengenai cara mengakses pembiayaan syariah yang lebih adil dan transparan. Kegiatan pengabdian ini dilaksanakan pada Kamis, 17 April 2025, di Mushola Lingkungan Kantin Royal, Serang, dengan melibatkan 20 peserta dari UMKM Dimsum Teh Ifat. Metode yang digunakan adalah pelatihan interaktif, diskusi, dan simulasi. Pre-test dan post-test dilakukan untuk mengukur peningkatan pemahaman peserta. Hasil pre-test menunjukkan bahwa hanya 40% peserta yang memahami akad syariah dengan baik, sedangkan setelah mengikuti pelatihan, hasil post-test menunjukkan peningkatan signifikan, dengan 85% peserta yang memiliki pemahaman yang lebih baik. Hasil kegiatan pengabdian menunjukkan adanya peningkatan signifikan dalam pemahaman peserta tentang keuangan syariah. Banyak peserta yang tertarik untuk mengakses pembiayaan syariah dari koperasi syariah atau BMT. Terbentuknya komunitas kecil UMKM Syariah untuk diskusi lanjutan menunjukkan bahwa kegiatan ini diterima dengan baik oleh masyarakat. Kegiatan ini berhasil meningkatkan literasi keuangan syariah di kalangan UMKM dan membuka akses pembiayaan yang lebih adil sesuai prinsip syariah.